Work-Related Intervention Programs: Desistance From Criminality and Occupational Integration Among Released Prisoners on Parole - Peled-Laskov, Ronit (International journal of offender therapy and comparative criminology, 2019)
The present research examines the integration into employment of prisoners on parole who had been under the supervision of the Prisoner Rehabilitation Authority during the period 2007-2010. The supervision program included rehabilitation in the community, with the emphasis on employment. The research compares integration in employment and rates of reincarceration for the supervised group with prisoners who had been released from prison after serving their full sentences. The findings indicate that among prisoners who had participated in the supervision program, there is better integration into employment, a higher wage level, and lower rate of reincarceration. Based on these results, it may be tentatively inferred that the supervision program possesses a high potential for reintegrating released prisoners into the community.